Fostering Environmental Awareness through Nature-Based Learning in Indonesian Early Childhood Education: Implications for Sustainable Development Goals - Alvina Damayanti; Mardalena Mardalena; Nurul Fauziah; Titin Sumarni; Gunawan Sahputra (Yayasan Zia Salsabila, 2025)
Despite the growing body of international research highlighting the benefits of nature-based learning for early childhood development, empirical evidence from developing countries, particularly Indonesia, remains limited. Most existing studies focus on cognitive or motor outcomes, leaving a gap in understanding how nature-based learning contributes to environmental awareness as part of Sustainable Development Goals (SDGs), especially SDG 4 (Quality Education) and SDG 13 (Climate Action). This study aims to examine the role of nature-based learning in fostering environmental awareness among early childhood learners in Indonesia. Employing a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews with teachers, and documentation of learning activities in early childhood education settings. The findings reveal that nature-based learning significantly enhances children’s engagement, ecological empathy, and responsible environmental behaviors through direct interaction with natural elements. Children demonstrated increased awareness by caring for plants, maintaining cleanliness, and reminding peers to protect the environment. This study contributes theoretically by reinforcing constructivist learning perspectives and empirically by providing context-specific evidence from Indonesia. Practically, the findings offer guidance for educators and policymakers to integrate nature-based learning as an effective strategy to support sustainable education and environmental stewardship from early childhood.